The Use of Hand Puppets in Discussion in Learning English Speaking Online for Class Students at Sentosa School, West Jakarta - Leroy Holman Siahaan; Dini Hidayati; Yon A.E; Iswandini Agustin; Syamsi Edi; Yanti Rusmiyati (Jurnal Pengabdian Masyarakat Formosa, 2022)
As an effort to prevent the spread of the Covid-19 virus, the government issued a policy for schools to implement online learning since March 2020. Was online learning effective during the Covid-19 pandemic. The object that the writer examined was the ability to speak and tell stories in class VII Sentosa School students. Because maybe online learning at home is less effective so students are asked to look for it from various sources. During online learning, teachers are required to be more innovative, and teachers must change and create new teaching methods so that teaching and learning activities are not boring and monotonous. Sentosa School grade 7 researchers and tutors conduct online storytelling activities in English. Researchers apply learning to tell stories with the media of hand puppets and discussion methods. This online field research was conducted using a quantitative approach with the discussion method.